2012
DOI: 10.4330/wjc.v4.i3.60
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for paroxysmal and persistent atrial fibrillation: An effective non-pharmacological tool?

Abstract: In Traditional Chinese Medicine, stimulation of the Neiguan spot has been utilized to treat palpitations and symptoms related to different cardiovascular diseases. We evaluated whether acupuncture might exert an antiarrhythmic effect on patients with paroxysmal or persistent atrial fibrillation (AF). Two sets of data are reviewed. The first included patients with persistent AF who underwent electrical cardioversion to restore sinus rhythm. The second included patients with symptomatic paroxysmal AF. All subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…150 In another study, acupuncture resulted in a significant reduction in the number and duration of symptomatic AF episodes in a small group of patients with paroxysmal AF. 151 These preliminary data need to be validated in a larger population, but suggest a potential role of acupuncture in the treatment of AF.…”
Section: Neural Stimulationmentioning
confidence: 99%
“…150 In another study, acupuncture resulted in a significant reduction in the number and duration of symptomatic AF episodes in a small group of patients with paroxysmal AF. 151 These preliminary data need to be validated in a larger population, but suggest a potential role of acupuncture in the treatment of AF.…”
Section: Neural Stimulationmentioning
confidence: 99%
“…Recent experimental 30 and clinical 31 studies have demonstrated that low-level nerve stimulation (that does not slow the heart rate and is nonsentient) applied at the auricular branch of the vagus nerve (the tragus of the outer ear) can consistently suppress AF. Other alternative therapies that have been proposed for the treatment of AF include acupuncture 32 and Yoga.…”
Section: Article See P 1276mentioning
confidence: 99%
“…Likewise, acupuncture significantly affected heart rate variability in healthy subjects. 8 A recent study 9 reported acupuncture efficacy similar to that of “the most active available antiarrhythmic drug”. With respect to these reports, it seems plausible that acupuncture effects could be additive to antiarrhythmic efficacy of conventional pharmacotherapy.…”
Section: Discussionmentioning
confidence: 96%